Achieving effectiveness by improving methods of using local phytopreparations in the treatment of inflammatory lesions of periodontal tissues - Axmadovich, Sobirov Alijon; Amrulloyevich, Gafforov Sunatullo; o`g`li, Odiljonov Javokhir Dilmurodjon; Sotvoldiyevich, Djambilov Ravshanbek; Sunnatulloyevna, Gafforova Sabina (International Journal of Innovative Research and Scientific Studies, 2025)
In recent years, the incidence of periodontal tissue pathologies in dental practice has markedly increased. However, conventional treatment approaches have often failed to yield satisfactory outcomes. Optimizing the oral microflora through the use of local phytotherapeutic agents represents a crucial solution for clinical practitioners in addressing periodontal diseases. This study aims to scientifically validate advanced methods for the application of local phytopreparations in the treatment of chronic hypertrophic gingivitis. A total of 326 patients diagnosed with "Moderate Chronic Hypertrophic Gingivitis" (K05.5) were enrolled between 2023 and 2025. Participants were divided into two age groups: 20–29 years (n=146) and 30–39 years (n=180), comprising 165 males and 161 females in total. The phytopreparations "Inflamdent," "Essential Oil Solution of Jasmine Flower," and "Infusion of Peganum Harmala" were administered either independently or in combination with "Chlorhexidine Bigluconate." Clinical-functional and clinical-laboratory assessments of oral tissues were performed at various treatment intervals. At baseline, microbial counts were similar across groups (1580.5±248.41 CFU/mL). Neutrophilic infiltration was 11.2±1.75 cells/field in Group 1, 10.3±1.95 in Group 2, and 9.2±1.34 in Group 3, with no statistically significant differences (p>0.05). Periodontal pocket depths were recorded as 4.8±0.06 mm, 4.2±0.09 mm, and 4.4±0.04 mm, respectively (p>0.05), and 100% of cases exhibited gingival bleeding. Following treatment, microbial (Candida spp.) prevalence decreased to 5.3%, 6.7%, and 6.3% across groups, respectively. Allergic manifestations were reduced to 9.8%, 9.6%, and 14.5%, while mucosal atrophy rates improved to 18.7%, 17.3%, and 16.3%. Comparative analysis conducted on Days 10 and 20 demonstrated statistically significant improvements through the use of the phytopreparations, both alone and combined with Chlorhexidine Bigluconate, as evidenced by univariate and multivariate statistical models. The application of phytopreparations, both individually and in combination with Chlorhexidine Bigluconate, demonstrated significant antiseptic, reparative, and anti-inflammatory activities, along with a reduction in complication rates and practical feasibility depending on clinical conditions. In terms of integral clinical effectiveness, the following ranking was established. 1."Inflamdent + Chlorhexidine Bigluconate," 2."Essential Oil Solution of Jasmine Flower + Chlorhexidine Bigluconate," 3."Infusion of Peganum Harmala + Chlorhexidine Bigluconate."